The Distribution of the Tax and Social Security Burden - Niklas Isaak; Philipp Jäger; Robin Jessen (Wirtschaftsdienst)
Abstract Using a cross-sectional analysis, this article investigates the burden of taxation and social security contributions across German households. The burden is determined with respect to household income as well as consumption level. Moreover, the different income groups’ contributions to public finance are illustrated. It can be demonstrated that for gross incomes of 24,000 euros, the average tax and contribution ratio amounts to 40 %. For household incomes of 80,000 euros, the ratio rises above 50 %.